Nanoparticles Engineered as Artificial Antigen-Presenting Cells Induce Human CD4+ and CD8+ Tregs That Are Functional in Humanized Mice - Sophia Giang (Frontiers in Immunology, 2021)
Artificial antigen-presenting cells (aAPCs) are synthetic versions of naturally occurring antigen-presenting cells (APCs) that, similar to natural APCs, promote efficient T effector cell responses in vitro. This report describes a method to produce acellular tolerogenic aAPCs made of biodegradable poly lactic-co-glycolic acid (PLGA) nanoparticles (NPs) and encapsulating IL-2 and TGF-β for a paracrine release to T cells. We document that these aAPCs can induce both human CD4+ and CD8+ T cells to become FoxP3+ T regulatory cells (Tregs). The aAPC NP-expanded human Tregs are functional in vitro and can modulate systemic autoimmunity in vivo in humanized NSG mice. These findings establish a proof-of-concept to use PLGA NPs as aAPCs for the induction of human Tregs in vitro and in vivo, highlighting the immunotherapeutic potential of this targeted approach to repair IL-2 and/or TGF-β defects documented in certain autoimmune diseases such as systemic lupus erythematosus.